Anti-osteoporotic activity of sialoglycoproteins isolated from the eggs of Carassius auratus by promoting osteogenesis and increasing OPG/RANKL ratio. (May 2015) - Xia, Guanghua; Wang, Shanshan; He, Min; Zhou, Xiaochun; Zhao, Yanlei; Wang, Jingfeng; Xue, Changhu
Highlights: Anti-osteoporotic activity of Ca- SGP is reported for the first time. Ca- SGP promoted osteogenesis. Ca- SGP increased OPG/RANKL ratio in MC3T3-E1 cells and bilateral ovariectomized rats. Ca- SGP improved tibia BMD of osteoporotic rats induced by bilateral ovariectomy. Ca- SGP is a novel and significant functional factor for the treatment of osteoporosis. Abstract: The anti-osteoporotic activities of a sialoglycoprotein isolated from the eggs of Carassius auratus ( Ca -SGP). Ca- SGP was composed of 14.33% protein, 62.81% hexose, and 19.72% N-acetylneuraminic acid (Neu5Ac). In vitro experimental results showed that Ca- SGP significantly increased MC3T3-E1 pre-osteoblastic cells' proliferation activities, promoted cell differentiation and mineralization as evidenced by increasing the contents or activities of major markers, i.e. collagen type I (COL I), osteocalcin (OCN), alkaline phosphatase (ALP) and bone nodules. Ca- SGP significantly augmented protein expressions and secretions of bone morphogenetic protein 2 (BMP-2) and osteoprotegerin (OPG), meanwhile, decreased that of receptor activator of nuclear factor κB ligand (RANKL). In vivo experimental data further revealed that Ca -SGP significantly reduced bone turnover rates, increased serum OPG/RANKL ratio and enhanced tibia bone mineral density (BMD) in the model rats of ovariectomized (OVX)-induced osteoporosis. These results suggest that Ca- SGP could improve osteoporosis by promoting osteogenesis and inhibiting bone resorption via increasing OPG/RANKL ratio, which indicates that Ca- SGP is a potential candidate functional factor for osteoporosis prevention.